Leopardi educatore degli Italiani: i giovani e la coscienza civile. Annotazioni - Michele Zedda (Firenze University Press, 2013)
Leopardi contributes effectually in education of young Italians, exhorting them to be proud of the past and rebel against foreign yoke. The Author hopes for an